Ethnicity homegrown: how the Lebanese-Argentines in Buenos Aires construct ethnicity - Kemp, Bianca (AUC Knowledge Fountain, 2013)
This work explores the construction of ethnicity among the Lebanese-Argentine population of Buenos Aires, Argentina. Although exact figures for the Lebanese population of Argentina are unknown, estimates hover around one and a half million (the national census does not require specification of ethnicity). The majority of these third-, fourth- and fifth-generation Lebanese-Argentines are descendents of early Syro-Lebanese immigrants. These migrants from Greater Syria culturally assimilated to their new “home” at the insistence of the Argentine government and xenophobic elite of the late 19th and early 20th centuries. Consequently, constructing a Lebanese-Argentine ethnic identity today means doing so when distance and passing time mean a cultural chasm between Lebanon and Buenos Aires. Just how do those of Lebanese heritage in Buenos Aires do it then? Some of them do not. The thesis argues that Lebanese-Argentine ethnic identity is non-essential. However, if and when descendants of Lebanese heritage do decide to construct a hybrid Lebanese ethnic identity in Buenos Aires, it is a simulation of what it means to be Lebanese. More explicitly, members of the Lebanese-Argentine ethnic group reference and express ethnic emblems germane to Lebanese ethnicity according to their understanding of Lebanese-ness. And the implications are profound. Those Lebanese-Argentines who subscribe to a Lebanese ethnic identity join an imagined global Lebanese ethnic community, one which has the potential to supersede national borders and influence the course of international politics.